Metode “Cross-cultural Competency Training” untuk Lulusan Sarjana Teknik di Indonesia - Ika S. Windiarti - Universitas Tridharma Balikpapan (APMMI - Asosiasi Profesi Multimedia Indonesia, 2017)
Abstract - Globalization encourages the distribution of workers to work in other countries. Engineer is one of the professions that enable people to work globally. Indonesian engineers must be ready to enter the global job market by developing their potential that requires not only hard skills. They also need soft skills to support their technical skills. This study is very important because it explores the perceptions, knowledge and experience of expatriate Indonesian engineers in working with culturally diverse engineering teams. The purpose of this research is to develop a training framework design to support the development of culturally aware education programs for Indonesian engineers planning to work outside Indonesia. This project has investigated the problems faced by Indonesian engineers working around the world. The engineers studied in this research work in various industries in various countries. The underlying belief in motivating research is that exploring cross-cultural adaptation issues in the workplace is the first step in identifying ways in which engineer professionalism can improve. This technology work is a framework and a syllabus of cross-cultural competence training for graduates of Bachelor of Engineering, which has never been developed by researchers in Indonesia let alone abroad. This paper reports the design of cross-cultural training frameworks for Indonesian engineering graduates that need to be built on several factors. These factors include language skills, reciprocal interaction, problem-solving decisions, and cross-cultural adaptation. The output of cross-cultural training will be used as their additional valuable skills to be ready for intercultural work. This framework is devoted to undergraduate graduates of Engineering that are not yet preprogrammed in the undergraduate curriculum in universities. Keywords: Cross-cultural Competency Training, engineering degree, soft skill Abstrak - Globalisasi mendorong distribusi para pekerja untuk bekerja di negara lain. Engineer adalah salah satu profesi yang memungkinkan orang bekerja secara global. Engineer Indonesia harus siap memasuki pasar kerja global dengan mengembangkan potensi mereka yang tidak hanya membutuhkan kemampuan hard skill. Mereka juga membutuhkan keahlian soft skill untuk mendukung keterampilan teknis mereka. Studi ini sangat penting karena mengeksplorasi persepsi, pengetahuan dan pengalaman engineer ekspatriat Indonesia dalam bekerja dengan tim teknik yang beragam secara budaya. Tujuan dari penelitian ini adalah untuk mengembangkan disain kerangka pelatihan untuk mendukung pengembangan program pendidikan yang sadar budaya bagi para engineer Indonesia yang berencana untuk bekerja di luar Indonesia. Proyek ini telah menyelidiki masalah yang dihadapi engineer Indonesia yang bekerja di seluruh dunia. Engineer yang diteliti dalam penelitian ini bekerja di berbagai industri di berbagai negara. Keyakinan yang mendasari memotivasi penelitian adalah bahwa mengeksplorasi isu-isu adaptasi lintas budaya di tempat kerja adalah langkah pertama dalam mengidentifikasi cara-cara di mana profesionalisme engineer dapat meningkat. Karya teknologi ini berupa kerangka kerja dan silabus pelatihan kompetensi lintas budaya bagi lulusan Sarjana Teknik, yang belum pernah dikembangkan oleh peneliti di Indonesia apalagi di luar negeri. Makalah ini melaporkan rancangan kerangka metode pelatihan lintas budaya untuk lulusan teknik Indonesia yang perlu dibangun terkait dengan beberapa faktor. Faktor-faktor tersebut meliputi kemampuan bahasa, interaksi timbal balik, keputusan pemecahan masalah, dan adaptasi lintas budaya. Output dari pelatihan lintas budaya akan digunakan sebagai keterampilan berharga tambahan mereka untuk siap dalam pekerjaan antarbudaya. Kerangka kerja ini dikhususkan untuk lulusan Sarjana Teknik yang belum terprogram dalam kurikulum program sarjana di perguruan tinggi. Kata Kunci: Cross-cultural Competency Training, sarjana teknik, soft skill